The effects of Mangifera indica L. leaf extract on sperm function - Amalia Shari; Ludira Dwi Novitasari (PT WIM Solusi Prima, 2026)
Male infertility remains a global health problem, contributing to approximately 50% of all cases of infertility in couples. One of the main factors causing decreased sperm quality is oxidative stress, which can damage cell membranes, reduce motility, and impair sperm viability. Mango leaves (Mangifera indica L.) are known to contain various bioactive compounds, such as mangiferin, flavonoids, tannins, saponins, triterpenoids, and steroids, which have strong antioxidant activity and potentially provide protection to germ cells in the testes. This paper aims to examine the effect of mango leaf extract on sperm function through parameters of motility, viability, and cellular protection mechanisms against oxidative stress. The results of the study indicate that antioxidant compounds in mango leaves play a role in neutralizing reactive oxygen species (ROS), maintaining membrane integrity, and supporting spermatogenesis. Thus, mango leaf extract has the potential to be a natural phytotherapeutic agent to improve sperm quality and support male reproductive health.